Changes in Pharmacokinetics and Pharmacodynamics of Losartan in Experimental Diseased Rats Treated with Curcuma longa and Lepidium sativum - Abdul Ahad; Mohammad Raish; Ibrahim Abdelsalam Abdelrahman; Yousef A. Bin Jardan; Mohd Aftab Alam; Abdullah M. Al-Mohizea; Fahad I. Al-Jenoobi (Pharmaceuticals, 2022)
The current study investigated “pharmacodynamics and pharmacokinetics interactions” of losartan with Curcuma longa (CUR) and Lepidium sativum (LS) in hypertensive rats. Hypertension was induced by oral administration of L-NAME (40 mg/kg) for two weeks. Oral administration of CUR or LS shows some substantial antihypertensive activity. The systolic blood pressure (SBP) of hypertensive rats was decreased by 7.04% and 8.78% 12 h after treatment with CUR and LS, respectively, as compared to rats treated with L-NAME alone. LS and CUR display the ability to potentiate the blood pressure-lowering effects of losartan in hypertensive rats. A greater decrease in SBP, by 11.66% and 13.74%, was observed in hypertensive rats treated with CUR + losartan and LS + losartan, respectively. Further, both the investigated herbs, CUR and LS, caused an increase in plasma concentrations of losartan in hypertensive rats. The AUC0-t, AUC0-inf and AUMC0-inf of losartan were increased by 1.25-fold, 1.28-fold and 1.09-fold in hypertensive rats treated with CUR + losartan. A significant (p < 0.05) increase in AUC0-t (2.41-fold), AUC0-inf (3.86-fold) and AUMC0-inf (8.35-fold) of losartan was observed in hypertensive rats treated with LS + losartan. The present study affirms that interactions between CUR or LS with losartan alter both “pharmacokinetics and pharmacodynamics” of the drug. Concurrent administration of losartan with either CUR or LS would require dose adjustment and intermittent blood pressure monitoring for clinical use in hypertensive patients. Additional investigation is necessary to determine the importance of these interactions in humans and to elucidate the mechanisms of action behind these interactions.